Assessment of the Physical Activity of Children with Asthma Bronchiale - Ildikó Balatoni; Tímea Kiss; György Balla; Ágnes Papp; László Csernoch (MDPI AG, 2024)
Physical activity is an especially important part of everyday life for children with chronic diseases. The aim of the study was to show whether asthma is a barrier to physical activity in our society. The correlations between the severity of the disease, body mass index, and physical activity were analyzed, and parents' opinions on whether children should participate in active sports were assessed. Physical activity of children with asthma was analyzed by questionnaires; 93 parents and their 93 children were involved in the survey. The age of children was 12.6 ± 3.5 years (mean ± SD), 69.9% were boys, 30.1% were girls. A total of 93.4% of the respondents participated in a physical education program and 56.5% also attended sporting activities on a regular basis. In terms of disease severity, 61.2% of the children had mild asthma, 37.6% moderate, and 1.2% severe, and 6.5% of the respondents also stated that their children's illness had been consistently or frequently limiting their performance concerning their school or home duties over the past four weeks. Of the parents surveyed, 12% felt that physical activity was not appropriate in the context of this disease. We concluded that fear of the consequences of physical activity depends largely on education, which should involve parents, teachers, and coaches.